For Richer, for Poorer: Bankers' Liability and Bank Risk in New England, 1867 to 1880 - KOUDIJS, PETER; SALISBURY, LAURA; SRAN, GURPAL (Journal of Finance, 2021)
ABSTRACT We study whether banks are riskier if managers have less liability. We focus on New England between 1867 and 1880 and consider the introduction of marital property laws that limited liability for newly wedded bankers. We find that banks with managers who married after a law had higher leverage, delayed loss recognition, made more risky and fraudulent loans, and lost more capital and deposits in the Long Depression of 1873 to 1878. These effects were most pronounced for bankers with the largest reduction in liability. We find no evidence that limiting liability increased firm investment at the county level.